(untitled) (Revista de Ciências Agroveterinárias, 2022)
Rainwater can be harvested from different roofs of rural buildings, which can be stored for multipurpose depending on its quality. This technical note describes rainwater quality collected directly from the atmosphere and after passing through four types of roofs that are: French ceramic (roof1/Agronomy school building), fiber cement (roof2/farm machinery shed), or French ceramic (roof3/sheep housing), and French ceramic (roof4- swine housing) located inside Agroveterinary School Campus (CAV/UDESC) in Lages, Santa Catarina state, Brazil. The parameters analyzed were pH, color, turbidity, dissolved oxygen, total coliforms, and thermotolerant coliforms. Results showed that pH “in natura” rainwater was variable and below 7.0 with an average of 6.02. However, after passing through the roof, there was an increase in the pH (average) to 6.34 (roof1), 6.90 (roof2), 7.14 (roof3) and 6.50 (roof4). The rainwater also presented variations in the parameters of turbidity, dissolved oxygen, and coliforms after passing through roofs. Thus, the rainwater can potentially be used for non-potable purposes, being then advised of their use without treatment for cleaning of nearby environments of these rural buildings, as well as the irrigation of trees and ornamental plants, among others.